Retrospective Cohort Study of Clinical Profile and IVIg Resistance in Children with Incomplete Kawasaki Disease in a Tertiary Care Center - Bhaskar Shenoy; Basavanhalli Chandregowda Arun (Pediatric Infectious Disease)
Background: Diagnosis of incomplete Kawasaki disease (KD) is a clinical challenge in the absence of a specific diagnostic test. Diagnosis of KD is based mainly on the typical constellation of clinical signs and symptoms. Incomplete KD is much more difficult to diagnose because they present with fewer clinical features. Hence, diagnosis and treatment are often delayed in such cases and the response to treatment with intravenous immunoglobulin (IVIg) is poor. A high index of suspicion is necessary to diagnose and manage the children presenting as incomplete KD. Objectives: To study the clinical spectrum of incomplete KD and to assess the response to IVIg therapy. Materials and methods: A retrospective cohort study of children with incomplete KD at a tertiary care hospital from January 2010 to April 2018. Diagnosis and treatment were based on American Heart Association (AHA) guidelines. Results: Fifty-four out of 94 KD cases were incomplete KD (57.4%). Most of the incomplete KD cases were in infants (48.1%). The mean duration of fever at diagnosis was 6.3 days in complete KD and 6.9 days in incomplete KD. Clinical manifestations were oral mucosal changes (79.6%), conjunctival injection (68.5%), and polymorphous exanthema (64.8%). Less common clinical manifestations were extremity changes (14.8%), cervical lymphadenopathy (33.3%), irritability (53.7%), diarrhea (31.4%), vomiting (20.3%), and Bacillus Calmette-Guerin (BCG) scar flare-up (11.1%). Coronary artery abnormality (CAA) was detected in 27 cases (50%). Forty-nine out of 54 cases showed clinical resolution to IVIg (90.7%), 5 were resistant to the first dose of IVIg, 4 responded to the second dose of IVIg, and 1 required infliximab. Conclusion: Incomplete KD is more often associated with CAA. Clinicians should have a high index of suspicion when fever persists for 5 days or more and is associated with any of the principal clinical manifestations. Few laboratory tests and echocardiography may assist in the early diagnosis and treatment. The majority of the children responded to IVIg.